2012
DOI: 10.1371/journal.pone.0034342
|View full text |Cite
|
Sign up to set email alerts
|

Plakophilin-3 Is Required for Late Embryonic Amphibian Development, Exhibiting Roles in Ectodermal and Neural Tissues

Abstract: The p120-catenin family has undergone a significant expansion during the evolution of vertebrates, resulting in varied functions that have yet to be discerned or fully characterized. Likewise, members of the plakophilins, a related catenin subfamily, are found throughout the cell with little known about their functions outside the desmosomal plaque. While the plakophilin-3 (Pkp3) knockout mouse resulted in skin defects, we find larger, including lethal effects following its depletion in Xenopus. Pkp3, unlike s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 88 publications
1
20
0
Order By: Relevance
“…We previously reported the morpholino-directed depletion of Pkp3 (>60% efficiency as shown in Figure 5B of Munoz et al, 2012) in early Xenopus laevis embryos results in altered neural crest establishment, as well as ectodermal fragility, touch hyposensitivity and heart defects [24]. Additionally, it has been reported that ETV1 localizes to neural crest cells during development and that other PEA3-subfamily members have roles in crest formation [51], [56].…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…We previously reported the morpholino-directed depletion of Pkp3 (>60% efficiency as shown in Figure 5B of Munoz et al, 2012) in early Xenopus laevis embryos results in altered neural crest establishment, as well as ectodermal fragility, touch hyposensitivity and heart defects [24]. Additionally, it has been reported that ETV1 localizes to neural crest cells during development and that other PEA3-subfamily members have roles in crest formation [51], [56].…”
Section: Resultsmentioning
confidence: 84%
“…Production of in vitro transcribed RNA was done following previously described methods [24]. Other constructs were reported previously and kindly provided by Dr. L. Shemshedini (Fes3xWT-Luc and MMP1-Luc) and Dr. R. Janknecht (MMP1 −87/−88) [48][50].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a role for Pkp3 as a conventional signalling molecule has not been demonstrated to date, there is mounting evidence to suggest that Pkp3 is actively involved in cellular stress response [3], morphogenesis [20] and cancer progression [21]. Interestingly, loss of juxta-membranous Pkp3 staining after heat shock, together with its expression in stress granules, has been reported previously [3], suggesting that Pkp3 might translocate to the cytosol when the cells are exposed to environmental stress.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of PG in zebrafish gave rise to heart defects at 48 hpf (Martin et al 2009). In Xenopus knockdown of PKP3 caused skin fragility, disruption in peripheral neural structures, altered establishment and migration of neural crest, and defects in ectodermal multiciliated cells (Munoz et al 2012).…”
Section: Dcs In Developmentmentioning
confidence: 99%